Reflection and Reflective Practice: Creating Knowledge through Experience - Ng, Stella L. (Seminars in Hearing, 2012)
Reflection and reflective practice are popular concepts in the health professions that have yet to be rigorously addressed in audiology literature. In this article, a select summary of the theoretical bases of reflection and reflective practice are presented, highlighted with practical examples. The potential for reflection and reflective practice to benefit audiology education and practice is discussed. A nondichotomous approach to including a reflective epistemology of practice in audiology is recommended. Also highlighted are the centrality of experience to knowledge development and attention to reflection-in-action as a way of being professional practitioners. Also, critical reflection is identified as crucial to uncovering assumptions that underlie our practices and challenging oppressive discourses and systems, toward moving the profession forward in a spirit of optimized patient/client care. Although this article is conceptually focused and not a broad literature review, some early research in audiology related to this topic is reviewed briefly and practical approaches to fostering reflective practice also are considered. Reflection and reflective practice offer generative possibilities for the rigorous development of knowledge based in practice and experience, crucial to balancing other practice approaches such as evidence-based practice.
Keywords: reflection; reflective practice; practice-based knowledge; experiential learning; education